In Situ Observation of Redox Dynamics and Surface Restructuring on Pt/CeO2 Catalysts - Yuye Li; Jianyu Cao; Zhongshi Zhang; Jing Xia; Xiangmin Meng (Crystals)
Heterogeneous catalysis has significant applications in energy conversion, chemical production, and environmental treatment. Among them, the supported catalyst Pt/CeO2 has attracted much attention due to its high catalytic activity and stability. While the particle size of the catalyst strongly influences its performance, the dynamic behavior and the underlying mechanism of the particle size effect under realistic reactions have not been fully clarified. Using in situ transmission electron microscopy and mass spectrometry, we systematically investigated the size-dependent surface restructuring of Pt nanoparticles supported on CeO2 in high-temperature redox environments. Larger Pt nanoparticles exhibited significant surface fluctuations during oxidation, which could be reconstructed under reducing conditions, with a slight rotation after the reaction cycle. In contrast, smaller Pt particles demonstrated greater stability, maintaining a constant size after the reaction while their surface structures continuously restructured into low-index crystal planes during oxidation. Mass spectrometry revealed water production during the catalytic process, highlighting a correlation between surface restructuring and reactivity. These findings advance the understanding of redox dynamics in noble metal catalysts and provide a theoretical basis for the design of more efficient and stable catalytic systems.